2021
DOI: 10.2147/dmso.s300250
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain After 20 Years of Age is Associated with Unfavorable Lifestyle and Increased Prevalence of Metabolic Disorders

Abstract: Purpose It is unclear what kind of modifiable lifestyle factors are associated with long-time weight gain in adulthood. To clarify the lifestyle behavior related to body weight gain since the age of 20 years, we explored the lifestyle risk factor, independently associated with excessive weight gain after 20 years of age as compared to those in subjects with a stable weight, with matching of age, gender, and the current body mass index (BMI). Patients and Methods From ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Disorders of these regulations, either positive or negative, attract somatic but also psychological complications, which require medical control and adequate scientific nutritional advice. Permanent self-regulation failures can lead to overweight and obesity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Disorders of these regulations, either positive or negative, attract somatic but also psychological complications, which require medical control and adequate scientific nutritional advice. Permanent self-regulation failures can lead to overweight and obesity [14].…”
Section: Introductionmentioning
confidence: 99%
“…This result echoes the findings of many previous studies. Takebe et al reported that, in participants aged older than 20 years, skipping breakfast was correlated with weight gain (OR 1.252, compared with a regular breakfast) [ 14 ]. A cross-sectional study in Iran showed that, among adult participants, breakfast consumption habits had a significant negative impact on the occurrence of metabolic syndrome (OR = 0.38) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…With social and economic development, the eating habits and lifestyles of Chinese individuals have undergone significant changes, especially those of working people. According to surveys, changes in eating habits are associated with the incidence of metabolic syndrome and contribute to the risk of cardiovascular and cerebrovascular diseases [ 12 14 ]. The working population comprises mostly young to middle-aged people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 Poor lifestyle behaviors can lead to excess BMI, resulting in hypertension, which consequently increases the cardiovascular risk. 36 Women undergo numerous hormonal changes throughout their different stages of life, which have significant effects on lipid metabolism. 33 However, more studies are needed to identify factors that lead to increased rates of overweight/obesity, which continuously threatens NCDs.…”
Section: Discussionmentioning
confidence: 99%